Photoperiodic time measurement and seasonal immunological plasticity - Stevenson, Tyler J. (Front Neuroendocrinol, 2014)
Seasonal variations in immunity are common in nature, and changes in day length are sufficient to trigger enhancement and suppression of immune function in many vertebrates. Drawing primarily on data from Siberian hamsters, this review describes formal and physiological aspects of the neuroendocrine regulation of seasonal changes in mammalian immunity. Photoperiod regulates immunity in a trait-specific manner, and seasonal changes in gonadal hormone secretion and thyroid hormone signaling all participate in seasonal immunomodulation. Photoperiod-driven changes in the hamster reproductive and immune systems are associated with changes in iodothyronine deiodinase-mediated thyroid hormone signaling, but photoperiod exerts opposite effects on the epigenetic regulation of reproductive neuroendocrine and lymphoid tissues. Photoperiodic changes in immunocompetence may explain a proportion of the annual variance in disease incidence and severity in nature, and provide a useful framework to help understand brain-immune interactions.